A skull of Plesiaceratherium gracile (Rhinocerotidae, Perissodactyla) from a new lower Miocene locality in Shandong Province, China, and the phylogenetic position of Plesiaceratherium. Issue 3 (3rd May 2016) - Lu, Xiaokang; Zheng, Xiaoting; Sullivan, Corwin; Tan, Jin
ABSTRACT: A well-preserved fossil skull from a new locality in Jijiazhuang, Changle County, Shandong Province, China, is attributable to Plesiaceratherium gracile . Other rhinoceroses from the nearby Shanwang Basin of Linqu County, Shandong, formerly described as Aceratherium sp. and Plesiaceratherium shanwangensis are also referable to P. gracile . The new skull demonstrates the presence in P. gracile of the following characters: continuous labial cingula on lower cheek teeth; skull roof with nearly flat profile; and external auditory pseudomeatus ventrally closed, proceeding dorsocaudally in a shallow groove. Comparison of Plesiaceratherium with Brachypotherium pugnator Matsumoto, 1921, suggests that referral of the latter to Plesiaceratherium should be reconsidered. A phylogenetic analysis based on 314 characters scored for 39 terminal taxa places Plesiaceratherium mirallesi in a basal position within Rhinocerotidae, and recovers other species of Plesiaceratherium as a clade that is well separated from B. pugnator and is sister to the [ Subchilotherium [ Acerorhinus [ Shansirhinus, B . pugnator [ Chilotherium ]]]] grouping. Based on this result and a reevaluation of the anatomy of ' P .' mirallesi, we propose that the genus Dromoceratherium should be revived to accommodate this species as D. mirallesi . The occurrence of P. gracile at Jijiazhuang indicates that the fossiliferous diatomaceous shales of this locality were deposited during the lower Miocene. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Lu, X., X. Zheng, C. Sullivan, and J. Tan. 2016. A skull of Plesiaceratherium gracile (Rhinocerotidae, Perissodactyla) from a new lower Miocene locality in Shandong Province, China, and the phylogenetic position of Plesiaceratherium . Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1095201.